Influence of temperature on the lubrication properties of Diesel, HVO, and pyrolysis oils from waste feedstocks - Kuszewski, Hubert; Jaworski, Artur; Szpica, Dariusz; Hunicz, Jacek; Woś, Paweł; Balawender, Krzysztof (Elsevier, 2026)
The increasing use of renewable and waste-derived fuels in diesel engines has intensified interest in their tribological performance, particularly under thermal conditions representative of real fuel system operation. While combustion characteristics of alternative fuels are well documented, their lubricity behavior at elevated temperature remains less understood. This study investigates the effect of temperature on the lubricity of five fuels: conventional diesel fuel (DF), hydrotreated vegetable oil (HVO), polypropylene-derived pyrolysis oil (PPO), polystyrene-derived pyrolysis oil (PSO), and tire pyrolysis oil (TPO). Lubricity tests were conducted using the high-frequency reciprocating rig (HFRR) method at preset temperatures of 30, 60, and 90 °C. Diesel fuel exhibited the best overall lubricity, mainly due to the presence of fatty acid methyl esters (FAME). In contrast, HVO showed poorer lubricity related to its paraffinic composition and lack of polar compounds supporting boundary film formation. Waste-derived pyrolysis oils demonstrated intermediate lubricity with varying temperature sensitivity. PPO showed relatively stable behavior at lower temperature, PSO exhibited significant deterioration with increasing temperature, and TPO provided relatively good lubricity at lower temperature but worsened at higher temperature due to viscosity reduction and water content. At the reference temperature of 60 °C, the wear scar diameter (WSD) ranged from 190.5 μm for diesel fuel to 326.0 μm for HVO, while PPO, PSO, and TPO yielded intermediate values of 264.0, 246.0, and 299.0 μm, respectively. In addition, a pronounced temperature dependence was observed, particularly for HVO (184–342 μm) and PSO (217.0–328.5 μm), whereas an opposite trend was identified for PPO (260.5–217.5 μm) over the temperature range of 30–90 °C. These findings highlight the importance of fuel composition and temperature in determining lubricity and support the development of suitable fuel formulations for diesel engine applications.
Keywords: fuel lubricity; hydrotreated vegetable oil; pyrolysis oil; waste-derived fuels; diesel engines; tribological properties; fi=Energiatekniikka|en=Energy Technology|